PENGARUH MEDIA AUGMENTED REALITY BERBASIS ASSEMBLR STUDIO TERHADAP KEMAMPUAN GEOMETRI KELOMPOK B DI TAMAN KANAK-KANAK KEMALA BHAYANGKARI 03 - Ummul Khairunisa; Setiyo Utoyo; Yaswinda; Tisna Syafnita (STKIP Subang, 2026)
Geometry ability is one aspect of cognitive development that needs to be developed from an early age because it plays a role in forming logical thinking, visual spatial and problem solving abilities. The results of observations at Kemala Bhayangkari 03 Kindergarten, Padang City showed that the geometry ability of group B children has not yet developed optimally. This is caused by the use of learning media that is still conventional so that children have not received concrete and interactive learning experiences. This study aims to determine the effect of the use of Augmented Reality media based on Assemblr Studio on the geometry ability of group B children at Kemala Bhayangkari 03 Kindergarten, Padang City. This study used a quantitative approach with a quasi-experimental method and a pretest-posttest control group design. The research sample consisted of 30 children consisting of 15 children in the experimental class and 15 children in the control class. Data were collected through geometry ability tests, then analyzed using normality tests, homogeneity tests and Independent Sample t-tests. The results of the study showed that there was a significant influence of the use of Assemblr Studio-based Augmented Reality media on children's geometric abilities with a significance value (Sig.2-tailed) of 0.001 <0.05. Thus, Assemblr Studio-based Augmented Reality media was effective in improving the geometric abilities of children in group B.